'Making' our way through: DIY and crafting communities in Toronto. Issue 1 (1st February 2013) - Hagedorn, Arden; Springgay, Stephanie
Drawing on an interview-based research project on Do-It-Yourself and crafting culture in Toronto, this essay explores three themes of "why craft"?: the need for personal gratification and identity-building; the desire to build a community with shared values; and the need to connect with a sense of humanity through labour in an increasingly technological and urban world. Though emerging craft communities may appear niche-like and closed off from mainstream forms of knowledge creation, discussion on these particularities provides us with examples of how crafting may benefit learning processes not originally connected to crafters. Examining what it means to craft in Toronto, and in larger independent DIY contexts may also make recognizable new models of learning that are based on communities of practice not typically associated with standards-based education.